PENDIDIKAN FILSAFAT UNTUK ANAK? PENDASARAN, PENERAPAN DAN REFLEKSI KRITIS UNTUK KONTEKS INDONESIA - Wattimena, Reza A.A. (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2016)
This article argues for the importance of philosophical education for elementary school's students in Indonesia. Philosophy can be understood as value education and also life education. Both are very important for the human's personality development. Therefore, ideally, this kind of education should be provided since childhood age. But, philosophy has different teaching method in compare to other sciences. It asks the children to think for themselves and try to find answers for their questions independently. It should not be a burden for children that already have loads of subjects to learn. The program philosophy for children should also bear in mind the existing cultural context that already exists in Indonesian society.